2023
DOI: 10.1186/s12944-023-01818-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized dietary lipids induce vascular inflammation and atherogenesis in post-menopausal rats: estradiol and selected antihyperlipidemic drugs restore vascular health in vivo

Abstract: Background Thermoxidation of edible oil through deep fat frying results in the generation of several oxidized products that promote lipid peroxidation and ROS production when eaten. Consumption of thermoxidized oil in post-menopausal conditions where the estrogen level is low contributes to cardiovascular disease. This study evaluates the role of estradiol and antihyperlipidemic agents (AHD) in restoring the vascular health of ovariectomized (OVX) rats fed with thermoxidized palm oil (TPO) and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…9 Several studies have shown that estrogen deficiency increases total cholesterol (TC), LDL-C levels and decreases high-density lipo-Lee H, et al Effects of Nutrition Education on CVD Risk Factors protein cholesterol (HDL-C) levels in post-menopausal people. [10][11][12][13][14][15] Post-menopausal people also have high levels of apolipoprotein (Apo)-B, which is a strong marker of coronary atherosclerosis. 16,17 Changes in appetite and physical and psychological changes such as depression can all occur due to menopausal factors.…”
Section: Introductionmentioning
confidence: 99%
“…9 Several studies have shown that estrogen deficiency increases total cholesterol (TC), LDL-C levels and decreases high-density lipo-Lee H, et al Effects of Nutrition Education on CVD Risk Factors protein cholesterol (HDL-C) levels in post-menopausal people. [10][11][12][13][14][15] Post-menopausal people also have high levels of apolipoprotein (Apo)-B, which is a strong marker of coronary atherosclerosis. 16,17 Changes in appetite and physical and psychological changes such as depression can all occur due to menopausal factors.…”
Section: Introductionmentioning
confidence: 99%